Study Of Students' Level Of Interest In Malang 17th Private Vocational School Volleyball Sport - Sadiyah, Anisa Maulia; Ernat, Yusvidha; Kusmawati, Wiwik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to determine the interest of students at SMPN 17 Malang towards volleyball. Thus, the approach used is quantitative descriptive research. The sample in this research was all class VIII students at SMPN 17 Malang, totaling 35 students. Data analysis techniques used to analyze interest in volleyball among students at SMPN 17 Malang. From the results of data analysis, only 6 students (17.14%) had a 'high' interest in volleyball. Meanwhile, 21 students (60%) had 'medium' interest in volleyball, and 8 students (22.85%) had 'low' interest in volleyball.